The Digital Era Challenge: Unraveling Hoaxes and Strengthening Social Media Ethics - Fairizal Rahman (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
This study aims to explore the challenges arising in the digital era, including the proliferation of hoaxes and ethical considerations in social media interactions. The research methodology employed is a qualitative approach through literature review analysis. Findings from this study highlight that the phenomenon of hoaxes often emerges on social media platforms, where content can be easily and rapidly disseminated without undergoing factual verification processes. Therefore, social media users need to be equipped with mature analytical skills and discretion in consuming content. Additionally, social responsibility is also crucial in the use of social media, both towards oneself and others. The conclusion of this research emphasizes the necessity for caution in disseminating information on social media to avoid the spread of misinformation or potentially harmful content.